Relation of JAK2 V617F allele burden and coronary calcium score in patients with essential thrombocythemia - Anžič Drofenik, Ajda (Radiology and oncology (Ljubljana), 2024)
JAK2 V617F (JAK2) mutation is associated with clonal hemopoiesis in myeloproliferative neoplasms as well as with faster progression of cardiovascular diseases. Little is known about the relationship between allele burden and the degree of atherosclerotic alteration of coronary vasculature. We previously reported that carotid artery stiffness progressed faster in patients with JAK2 positive essential thromocythemia (ET) patients. After a four-year follow-up we investigated whether mutation burden of a JAK2 allele correlates with a higher coronary calcium score. Patients and methods. Thirty-six patients with JAK2 positive ET and 38 healthy matched control subjects were examined twice within four years. At each visit clinical baseline characteristics and laboratory testing were performed, JAK2 mutation burden was determined, and coronary calcium was measured. Results. JAK2 allele burden decreased in 19 patients, did not change in 5 patients, and increased in 4 patients. The coronary calcium Agatston score increased slightly in both groups. Overall, there was no correlation between JAK2 allele burden and calcium burden of coronary arteries. However, in patients with the JAK2 mutation burden increase, the coronary calcium score increased as well. Conclusions. The average JAK2 allele burden decreased in our patients with high-risk ET during the four-year period. However, in the small subgroup whose JAK2 mutation burden increased the Agatston coronary calcium score increased as well. This finding, which should be interpreted with caution and validated in a larger group, is in line with emerging evidence that JAK2 mutation accelerates atherosclerosis and can be regarded as a non-classical risk factor for cardiovascular disease.
Keywords: aleli JAK2 V617F; esencialna trombocitemija; koronarna kalcifikacija; mutacija JAK2 V617F